Circ_0116061 regulated the proliferation, apoptosis, and inflammation of osteoarthritis chondrocytes through regulating the miR-200b-3p/SMURF2 axis - Zheng, Wei (J Orthop Surg Res, 2021)
BACKGROUND: Circular RNA (circRNA) has been shown to be associated with osteoarthritis (OA) progression. Circ_0116061 has been found to be highly expressed in OA cartilage tissues, but its role and mechanism in OA progression remain unclear. METHODS: Expression levels of circ_0116061, microRNA (miR)-200b-5p, and Smad ubiquitin regulatory factor 2 (SMURF2) were detected using quantitative real-time PCR. The proliferation and apoptosis of cells were measured using cell counting kit 8 (CCK8) assay, colony formation assay, and flow cytometry. Furthermore, the protein levels of proliferation-related marker, apoptosis-related markers, inflammatory factors, and SMURF2 were tested using western blot (WB) analysis. In addition, the interaction between miR-200b-3p and circ_0116061 or SMURF2 was examined using dual-luciferase reporter assay and biotin-labeled RNA pull-down assay. RESULTS: Circ_0116061 and SMURF2 were highly expressed, and miR-200b-3p was lowly expressed in OA cartilage tissues. Knockdown of circ_0116061 could promote the proliferation and inhibit the apoptosis and inflammation of OA chondrocytes. MiR-200b-3p could be sponged by circ_0116061, and its inhibitor could reverse the regulation of circ_0116061 silencing on the biological functions of OA chondrocytes. SMURF2 was a target of miR-200b-3p, and its expression was positively regulated by circ_0116061. Silencing of SMURF2 also could enhance the proliferation and suppress the apoptosis and inflammation of OA chondrocytes. Furthermore, the regulation of circ_0116061 silencing on the biological functions of OA chondrocytes also could be reversed by SMURF2 overexpression. CONCLUSION: Our data showed that circ_0116061 might regulate the miR-200b-3p/SMURF2 axis to promote the progression of OA.